Transformasi limbah kayu menjadi rak fungsional kamar mandi sebagai solusi inovatif untuk interior berkelanjutan - Muhammad Rangga Al Aghni; Jati Widagdo; Achmad Zainudin (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Wood waste is small, irregular pieces of furniture industry waste that are often discarded in the Jepara region, especially in Jepara. The amount of wood waste from the furniture industry increases daily and remains largely unmanaged. This study aims to explore the use of wood waste as a functional bathroom interior shelf, combining it with metal rims as an innovative solution. To reduce waste and promote sustainability, the study employed an upcycling method to transform waste materials into high-value products. The creative process of upcycling involves 1) waste material identification, 2) design planning, and 3) innovative manufacturing techniques. The waste identification process generates creative ideas, which are then translated into design sketches to facilitate the selection of the best ideas for implementation into a product that aligns with the concept. The results of the study indicate that transforming wood and rim waste into a bathroom shelf not only reduces environmental impact but also creates an aesthetically pleasing and functional product. The creative process of upcycling involves waste material identification, design planning, and innovative manufacturing techniques. This research contributes to the development of sustainable interior design and provides a practical alternative for waste management.